Suppression of microglial Ccl2 reduces neuropathic pain associated with chronic spinal compression - Li, Quan; Yang, Zongde; Wang, Kun; Chen, Zhi; Shen, Hongxing (Frontiers in Immunology, 2023)
Introduction Chronic spinal compression is a common complication of spinal cord injury (SCI), which can lead to spinal stenosis or herniated discs. The ensuing neuropathic pain is often associated with the activation of microglia. In this investigation, our objective was to explore whether modifying the levels of chemokine (C-C motif) ligand 2 (Ccl2) in microglia could alleviate neuropathic pain resulting from chronic spinal compression. Methods We used a public database to look for major altered gene associated in a SCI model established in rats. We then employed adeno-associated virus (AAV) vectors, expressing siRNA for the identified significantly altered gene under a microglia-specific TMEM119 promoter. We also tested the impact of this treatment in microglia in vivo on the severity of chronic spinal compression and associated pain using a ttw mouse model for progressive spinal compression. Results We identified chemokine (C-C motif) ligand 2 (Ccl2) as the primary gene altered in microglia within a rat SCI model, utilizing a public database. Microglial Ccl2 levels were then found to be significantly elevated in disc specimens from SCI patients diagnosed with chronic spinal compression and strongly correlated with the Thompson classification of the degeneration level and pain score. Depletion of Ccl2 in microglia-specific TMEM119 promoter were developed to transfect mouse microglia in vitro, resulting in a proinflammatory to anti-inflammatory phenotypic adaption. In vivo depletion of Ccl2 in microglia mitigated the severity of chronic spinal compression and related pain in ttw mice, likely due to significant changes in pain-associated cytokines and factors. Conclusion Disc microglia expressing high levels of Ccl2 may contribute to chronic spinal compression and SCI-associated pain. Therapeutically targeting Ccl2 in microglia could offer a potential avenue for treating chronic spinal compression and SCI-associated pain.